Solubility, sorption isotherms and thermodynamic parameters of β-cyclodextrin complexes with poplar propolis components: Practical implicances - Dos Santos Ferreira, Cristina Isabel (2022)
The aim of this work was to establish experimental conditions to improve water solubility of poplar propolis components by complexation with β-cyclodextrin (BCD). Water sorption properties, stability constants and thermodynamic parameters of the encapsulation process were studied. Propolis greatly modified BCD sorption isotherms, being water sorption lower in propolis-BCD system. These results are consistent with the displacement of water molecules from the inner cavity of the BCD by propolis components and evidence propolis component-BCD interactions. Results showed a positive linear relationship between phenolic compounds water solubility and the BCD amount in aqueous solution. The solubility increase depends on the polarity and spatial geometry of these components. Phase solubility data indicated the formation of 1:1 M ratio complexes and studies at different temperatures allowed to calculate the stability constants and the thermodynamic parameters of the inclusion process. The negative ΔH (−22 kJ mol−1) and ΔG (−12.8 kJ mol−1) values indicate that the inclusion of propolis components in BCD is an exothermic and spontaneous process, respectively, that is mainly enthalpy driven. The obtained ΔS (-32 J mol−1.K−1) is typical of low energy interactions. Present results could be of interest to develop aqueous propolis formulations avoiding the use of organic solvents and without undesirable tastes or flavors.